2005
DOI: 10.7202/050360ar
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Duty of Fair Representation in Union Grievance Decisions

Abstract: Le devoir de juste représentation des syndicats a évolué de façon à protéger les droits contractuels des salaries pris individuellement contre les atteintes à ceux-ci de la part des dirigeants syndicaux. Cet article rend compte des résultats d'une enquête auprès des dirigeants syndicaux au sujet de l'effet du devoir de juste représentation en matière de procédure de règlement de griefs. L'enquête a confirmé les résultats des recherches antérieures qui démontrent que les plaintes concernant la juste représentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a subsequent study, Knight (1987b) surveyed 88 British Columbia union staff members to examine the impact of DFR expectations on grievance handling. The survey responses indicated that most staff who handled grievances were aware of the potential for DFR complaints, and ensured that they undertook actions (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a subsequent study, Knight (1987b) surveyed 88 British Columbia union staff members to examine the impact of DFR expectations on grievance handling. The survey responses indicated that most staff who handled grievances were aware of the potential for DFR complaints, and ensured that they undertook actions (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%